Problemática del análisis de conducta entre la ciencia y la tecnología: aportaciones metodológicas del Método VERA = Theoretical problems of behavior analysis between science and technology: methodological contributions of the VERA Method - Pérez-Fernández, Francisco (Behavior & Law Journal, 2022)
Criminal profiling techniques are immersed in a state of review in terms of their methodologies and theoretical assumptions. Its empirical contrast, its expert value and its validity as police investigation tool are debated. The pillars on which their principles largely rest, such as the homology thesis, the ideas of consistency and behavioral differentiation, face conflicting evidence. For this reason, two major concerns have arisen regarding the criminal profiling technique: its usefulness and its methodological rigor. To resolve this situation, is necessary an in-depth review of their proposals and the use of those that prioritize methodological rigor with an objective of verifiable utility without the need to accept psycho-criminological theories that have not been sufficiently contrasted. One of these proposals is the VERA Method for the elaboration of psychological profiles of unknown aggressors, developed with a vocation of utility without renouncing the contributions of the scientific method.